Chemical–mechanical wear of monocrystalline silicon by a single pad asperity. (September 2017) - Wang, Lin; Zhou, Ping; Yan, Ying; Zhang, Bi; Kang, Renke; Guo, Dongming
Abstract: Chemical mechanical polishing (CMP) processes have been widely used in many fields with the ability to obtain an ultra-smooth surface. However, a comprehensive understanding of the material removal mechanisms at single pad asperity scale is still lacking, where a large number of abrasive particles are entrapped in the pad asperity/wafer microcontact area and then participate into polishing. In this study, two different pad asperity-scale material removal models are derived based on the indentation-sliding mechanism and chemical bond removal mechanism, respectively. Furthermore, series of pad asperity scale polishing tests are conducted on monocrystalline silicon wafer surface by using a polyoxymethylene (Pom) ball to mimic a single pad asperity. The results show that under the asperity-scale, material removal is highly related to the chemical reaction time between sequential asperity-wafer interactions, indicating the chemical control of the removal rate by controlling the reacted layer thickness. In particular, it is found that the reacted layer thickness follows the diffusion equation, and atoms within not only the topmost surface layer, but also the next or deeper layer can participate in the chemical reaction. Material removal behavior can be well explained by the dynamic formation and breakage of the interfacial chemical bonds between the Si atoms and SiO2 particles, rather than the indentation-sliding mechanism. It is further confirmed that no damage, such as lattice distortion or dislocation, is found in the subsurface of a wafer by the high-resolution transmission electron microscopy (HRTEM). This study provides new insights into the material removal mechanisms in CMP at an asperity-scale. Highlights: Proposing a novel method for investigating the pad asperity scale MRR in CMP. Establishing two pad asperity scale MRR models under different remove mechanisms. The atoms in the second or inner layers can still be reacted in CMP process. Reacted layer thickness is consistent with the diffusion-controlled reaction model.